A collaborative, multi-sectoral approach to implementing a social prescribing initiative to alleviate social isolation and enhance well-being amongst older people. Issue 1 (10th July 2020) - Wilkinson, Emma Killbery; Lees, Amanda; Weekes, Sarah; Duncan, Gillian; Meads, Geoffrey; Tapson, Kit
Abstract : Purpose: In 2019, St Johns Winchester, a CQC-registered charity, launched the Hand in Hand (HiH) Service, a social prescribing (SP) initiative to alleviate social isolation/loneliness amongst older people via integration between primary care and the third sector. Arising from collaborative stakeholder reflection, this article explicates processes instigated to plan, implement and evaluate the HiH service which has been locally recognised as an exemplar of good practice. It aims to fill a gap in the literature which has hitherto lacked contextual description of the drivers, mechanisms and processes of SP schemes, leading to confusion over what constitutes SP and which models can work. Design/methodology/approach: The article defines the context of, drivers for and collaborative process followed to implement and evaluate HiH and reflects on challenges, facilitators and key points for transferable learning. Early evaluation findings are presented. Findings: Key features underpinning the success of the pilot phase were: having clear referral pathways, working collaboratively with health and voluntary sector partners, building relationships based on trust, adherence to high-quality standards and governance, a well-trained team of volunteers and access to up-to-date information source. There remains a disparity between the urgent need for rigorous evaluation data and the resources available to produce it. Originality/value: The article offers a novel contribution for those planning SP at the level of practice and policy and for the developing field of SP evaluation.